A typology of stigma within organizations: Access and treatment effects. (10th April 2018) - Summers, James K.; Howe, Michael; McElroy, James C.; Ronald Buckley, M.; Pahng, Phoebe; Cortes‐Mejia, Sebastian
Summary: Stigmatization is a process by which certain individuals are devalued and alienated from specific types of social interactions, because they are perceived to possess a negatively valenced characteristic (e.g., age, gender, and medical condition). Due to its diverse and context‐driven nature, stigmatization potentially affects a large percentage of the population. Consequently, many individuals are likely victimized by stigmatization processes in a particular situation and subsequently may be deprived of the organizational opportunities available to nonstigmatized individuals. The purpose of this paper is to review and organize the literature by drawing on a suggested typology of stigmas found in organizations. We ground this novel typology in both the stigmatization and management literatures, incorporating the dimensions of controllability and visibility of stigmatizing attributes as well as whether or not the attribute is protected under federal law. Because all stigmatizing characteristics are not equally deleterious, we present 8 separate groups of stigmas and the differential effects that each have on stigmatized individuals' opportunities within organizations (i.e., access and treatment discrimination). Further, we outline mechanisms (i.e., imputed characteristics) that underlie the differential treatment afforded those who are stigmatized. We then provide a research roadmap to better understand the role stigmas play in organizations moving forward.